Ser tatuador/a, ser artista: uma análise sociológica sobre os processos de artificação da tatuagem na capital paulista - Patriota Pereira, Beatriz (2021)
This research proposes an empiric study on the tattoo artification processes and starts with the following question: what are the strategies and discourses developed by male and female tattoo artists for the practice be artified? Since the 1980s and 1990s, in Brazil, tattooing has gone through the processes of professionalization, commercialization, commodification, sanitation, regulation, field standardization and, finally, artification, changing the ways it is conceived socially. Thus, the research aims to understand the power relations and negotiations between male and female tattoo artists regarding the knowledge construction about artification practice in São Paulo. It also seeks to analyze how the association between tattoo and art materialized in the fields of production, mediation and reception; understand the dimensions negotiated by male and female tattooists in order to construct the artistic value of tattoo; and, finally, to reflect how generation, gender, race and class differences reverberate in tattoo artification. These purposes will be achieved through participant observation in the institutions that discuss tattoo as art, semi-structured interviews with male and female tattooists inserted in the process of tattoo artification in São Paulo, bibliographic research and theoretical discussion on body modification and art.